Integrating Language And Culture In The Classroom: A Case Study Of A Bilingual School In Indonesia - Surya Hoirul Ahsan Dalimunthe; Irwan Irwan; Deminar Nababan; Suhailasari Suhailasari; Rudy Dermawan; Melly Lestari; Kumala Sari (LPPM Universitas PGRI Sumatera Barat, 2024)
Learning is an acculturation process, serving as a vehicle for transmitting scientific and national cultures to the next generation, as well as adopting and developing them within a community. Learning itself has its own culture, including traditions, assumptions, and scientific rules, which make it a distinct cultural system. Occasionally, changes in science, technology, and societal needs have led to shifts in the culture of learning. Society is comprised of individuals who form groups based on shared characteristics. For a group to be considered a community, they must have commonalities that distinguish them from other groups and ultimately shape their culture. Culture is the social cement that binds individuals together through shared principles, ideals, attitudes, beliefs, and ways of thinking. The distinction between society and culture is evident, as society cannot exist without culture. In the absence of culture, there can be no community.